Analysing (In)formal Mechanisms of Crime Control: A Cross-Cultural Perspective - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 1988)
These include Saudi Arabia, West Africa, Morocco, Italy, Venezuela, China, Japan, Yugoslavia, Egypt, and the Federal Republic of Germany. Part 1 explores informal crime control mechanisms at the level of analytical concepts, particularly formalization, the ideology of informalisms, and structural components of all crime control mechanisms. Part 2 contains individual contributions examining the development, structure, operation, and perception of various informal control processes; socialization processes involved in the operation of these mechanisms; and their relationship to formal control mechanisms. Among specific mechanisms examined are the family, religion, friendship groups and voluntary organizations, therapeutic communities, the Chinese Public Security Committee, political organizations, the workplace, and traditional cultural customs and values. Finally, Part 3 assesses the relevance of formalization to the control of crime and identifies characteristics of formalization. Indicators of crime control potential of a given mechanism are proposed for evaluating effective policies.